Design of state and output feedback pole placement controller in the presence of slow-rate integrated measurement. (January 2020) - Ramezani Khosro, Elham; Fatehi, Alireza
Highlights: Slow-rate integrated measurement (SRTM) is the mean of the variable at each period. State feedback and output feedback controllers are designed for plant having SRTM. The Kalman filter is modified to estimate slow and fast-rate states using SRTM. Output feedback controller is designed using a novel I/O model of the SRTM plant. Simulation and experimental results evaluate efficiency of the proposed methods. Abstract: Lab measurements in the industrial processes are either through instantaneous measurement at a specific time instance, known as Slow-Rate inStantaneous Measurement (SRSM), or through Slow-Rate inTegrated Measurement (SRTM), in which some amount of material is gradually collected for a period of time; so, the average of the collected material during that period is measured. In this paper, control of a system under SRTM is studied for the first time. Pole placement state feedback with feedforward controller is proposed so that both SRTM and conventional fast-rate output can track their step reference input. This controller comprises a periodically time-varying gain and an observer to estimate the slow-rate instantaneous state variable at the sampling instances. An observability condition is studied, and a modified Kalman filter is established to estimate slow-rate instantaneous state variable using SRTM. In the next step, two modified pole placement output feedback controllers are designed using SRTM. In the first control system, the aim is to track a slow-rate integrated reference input. In the second controller, fast-rate reference input is introduced to the control system. The performance of the proposed methods is evaluated through both simulation study in a pH neutralization process plant and experimental implementation on a laboratory scale Quadruple Tank pilot plant.